2007
DOI: 10.1088/0022-3727/40/13/014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Au diffusion on structural, electrical and optical characteristics of CdTe thin films

Abstract: Diffusion of Au and its effects on structural, electrical and optical properties of CdTe films fabricated by the close-spaced sublimation technique have been investigated. Diffusion of Au was studied in the range 400–550 °C using energy dispersive x-ray fluorescence analysis. Au-doped and un-doped CdTe films were characterized by x-ray diffraction (XRD), electrical and optical absorption measurements. The temperature dependence of the diffusion coefficient of Au in CdTe films is described as D = 4.4 × 10−7exp(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Thus, the GBs with a high density of vacancies facilitate the rapid diffusion process. 136 It is suggested that grain boundary diffusion is a very likely mechanism for the impurity transport into the device and dopant diffusion coefficient are enhanced at GBs. 127,131 GBs in CdTe have downward bending, while those in CdTe 1Àx S x have upward bending.…”
Section: Technical and Environmental Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the GBs with a high density of vacancies facilitate the rapid diffusion process. 136 It is suggested that grain boundary diffusion is a very likely mechanism for the impurity transport into the device and dopant diffusion coefficient are enhanced at GBs. 127,131 GBs in CdTe have downward bending, while those in CdTe 1Àx S x have upward bending.…”
Section: Technical and Environmental Issuesmentioning
confidence: 99%
“…116 For Au as back contact, Au diffusion in CdTe can be described by the Arrhenius expression D ¼ 4.4 Â 10 À7 exp(À0.54 eV)/kT with a relatively low activation energy (0.54 eV). 136 The diffusion of Au into grains proceeds by the dissociative mechanismthe migrating impurity quickly moves by way of interstitial sites and settles in vacancies. The mechanism of Au diffusion in CdTe takes place in two ways: (i) by fast migration along the GBs; (ii) by relatively slow migration into grains which are characterized by low and high activation energies, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Though three temperature dependencies of In, Ga and Tl diffusivity intersect in the same point at T = 1390 K (i.e. in CdTe molten state), it can't be a solid base for a conclusion about the data fit to the NMR [37,38] Hg [39,40] *Zn [35] Zn [36,59] ln(D 0 , cm 2 /s) [24,26,27] Cu [25,28,29] *Ag [30] Ag [28,31] Au [34] ln(D Li [22] Na [23] Al [22] *Ga [41,42] In [23,43,48] *In [44][45][46][47] *Tl [49] *Ge [50] *Sn [51] ln(D T 0 (a) (b) Fig. 4 (a) The plot of the ln D 0 versus DE a for the diffusivity of the Groups I, III and IV impurities in CdTe crystals and thin films.…”
Section: Diffusion Of Ia Iiia and Iva Groups Impuritiesmentioning
confidence: 99%
“…For the homojunction devices fabricated here the benefits of microstructural changes obtained through annealing 29,30 are offset by type conversion of part or all of the deposit 23,24 as well as diffusion from the gold contacts, where applicable. 31 The use of different contact materials for the two electrodes might enable improvement through annealing by differential doping around the metallizations as well as improve the electrical properties of the contacts. One might also cap the metallization͑s͒ with conducting oxide or nitride ͑or grow it͒ to decrease recombination and act as a diffusion barrier if it does not degrade the CdTe deposition process.…”
Section: H658mentioning
confidence: 99%